Differential accumulation of plant defense gene transcripts in a compatible and an incompatible plant-pathogen interaction. - Bell, J N (1986)
Phenylalanine ammonia-lyase and chalcone synthase catalyze the first reaction of phenylpropanoid biosynthesis and the first reaction of a branch pathway specific for flavonoid-isoflavonoid biosynthesis, respectively. These enzymes are key control elements in the synthesis of kievitone, phaseollin, and related isoflavonoid-derived phytoalexins. RNA blot hybridization with 32P-labeled cDNA sequences was used to demonstrate marked accumulation of phenylalanine ammonia-lyase and chalcone synthase mRNAs in excision-wounded hypocotyls of Phaseolus vulgaris L. (dwarf French bean) and during race-cultivar-specific interactions between hypocotyls of P. vulgaris and the partially biotrophic fungus Colletotrichum lindemuthianum, the causal agent of anthracnose. In an incompatible interaction (host resistant), early concomitant accumulation of phenylalanine ammonia-lyase and chalcone synthase mRNAs, localized mainly but not entirely in tissue adjacent to the site of infection, was observed prior to the onset of phytoalexin accumulation and expression of localized, hypersensitive resistance. In contrast, in a compatible interaction (host susceptible) there was no early accumulation of these transcripts; instead, there was a delayed widespread response associated with phytoalexin accumulation during attempted lesion limitation. Two-dimensional gel electrophoresis of [35S]methionine-labeled polypeptides synthesized in vitro by translation of isolated polysomal RNA demonstrated stimulation of the synthesis of characteristic sets of phenylalanine ammonia-lyase and chalcone synthase isopolypeptides in directly infected tissue and distant, hitherto uninfected tissue in both compatible and incompatible interactions. Our data show that specific accumulation of plant defense gene transcripts is a key early component in the sequence of events leading to expression of defense responses in wounded tissue and in infected tissue during race-cultivar-specific interactions and that an elicitation signal is transmitted intercellularly in response to infection.